Accurate energy bands calculated by the hybrid quasiparticle self-consistent GW method implemented in the ecalj package. (31st March 2016) - Deguchi, Daiki; Sato, Kazunori; Kino, Hiori; Kotani, Takao
Abstract: We have recently implemented a new version of the quasiparticle self-consistent GW (QSGW) method in the ecalj package released at http://github.com/tkotani/ecalj . Since the new version of the ecalj package is numerically stable and more accurate than the previous versions, we can perform calculations easily without being bothered with tuning input parameters. Here we examine its ability to describe energy band properties, e.g., band-gap energy, eigenvalues at special points, and effective mass, for a variety of semiconductors and insulators. We treat C, Si, Ge, Sn, SiC (in 2H, 3C, and 4H structures), (Al, Ga, In) × (N, P, As, Sb), (Zn, Cd, Mg) × (O, S, Se, Te), SiO2, HfO2, ZrO2, SrTiO3, PbS, PbTe, MnO, NiO, and HgO. We propose that a hybrid QSGW method, where we mix 80% of QSGW and 20% of LDA, gives universally good agreement with experiments for these materials.